Analisis Faktor Risiko Kecelakaan Speedboat di Perairan Indonesia dan Strategi Pencegahannya - Iskandar; Fahmi Umasangadji; Imam Sutrisno (CV. Creative Tugu Pena, 2024)
Speedboat accidents in Indonesian waters are still frequent, causing casualties and property damage. This study aims to analyze the risk factors and formulate prevention strategies for speedboat accidents. The research method used is descriptive with a qualitative approach. Data were collected from literature, statistical data, and interviews with experts. The results showed that human factors are the main risk factors, followed by technical and environmental factors. The recommended prevention strategies include improving driver training and education, implementing strict regulations and supervision, improving speedboat quality, strengthening early warning systems, and community participation.